Quantitative Salivary Proteomic Differences in Oral Chronic Graft-versus-Host Disease - Bassim, Carol W (Springer US, 2012)
PURPOSE: Chronic graft-versus-host disease (cGVHD) is a severe immunological complication that occurs after allogeneic hematopoietic stem cell transplantation (HSCT). Although oral cGVHD occurs in >25 % of cGVHD patients and leads to decreased quality of life, its etiology is poorly understood. The present retrospective cross-sectional analysis of oral cGVHD patients sought to (1) test the feasibility of liquid chromatography tandem mass spectrometry (LC-MS/MS) to identify protein biomarkers of oral cGVHD and (2) to gain a clearer understanding of salivary proteins impacted by oral cGVHD. METHODS: Using unstimulated whole saliva, we compared pooled saliva from five patients with a diagnosis of moderate or severe oral cGVHD, with a gender-and age- matched pool of five cGVHD patients with no oral mucosal findings. LC-MS/MS was used to identify salivary proteins, followed by Ingenuity Pathway Analysis (IPA). Selected mass spectrometric findings, including lactotransferrin, lactoperoxidase, and albumin, were confirmed by targeted label-free quantification. RESULTS: LC-MS/MS led to confident identification of 180 proteins. Of these proteins, 102 changed in abundance at least 2 fold, including 12 proteins identified only in the No oral cGVHD group. Downregulation of ~0.4 fold was confirmed for both lactotransferrin and lactoperoxidase in Oral cGVHD saliva using targeted label-free quantification. IPA analysis implicated pathways involved in cellular metabolism and immunoregulation. CONCLUSIONS: Reduction of salivary lactoperoxidase, lactotransferrin, and several cysteine proteinase inhibitor family proteins suggests impaired oral antimicrobial host immunity in cGVHD patients. This shotgun proteomic analysis of oral cGVHD saliva using targeted label-free quantification of select proteins supports the use of mass spectrometry for future validation in a large patient population as noninvasive tests for screening, early detection, and monitoring of cGVHD. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10875-012-9738-4) contains supplementary material, which is available to authorized users.